The College Wealth Divide: Education and Inequality in America, 1956-2016 - Alina K. Bartscher; Moritz Kuhn; Moritz Schularick (Center for Economic Studies and ifo Institute (CESifo), 2019)
Using new long-run microdata, this paper studies wealth and income trends of college and non-college households in the United States since 1956. We document the emergence of a substantial college wealth premium since the 1980s, which is considerably larger than the college income premium. Over the past four decades, the wealth of American households with a college-educated head has tripled. By contrast, the wealth of non-college households has barely grown in real terms over the same period. Part of the rising wealth gap can be traced back to systematic portfolio differences between college and non-college households that give rise to different exposures to asset price changes. Non-college households have a lower exposure to the equity market and have profited much less from the recent surge in the stock market. We also discuss the importance of financial literacy and business ownership for the increase in wealth inequality between college and non-college households.
Keywords: I24; E21; D31; 330; wealth; inequality; education; college wealth premium